SENTRAINDUSTRI SEBAGAI PILIHAN PEMBANGUNAN EKONOMI DAERAH - Edhi Sutanto K. (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2004)
Sentra induslri (industrial cluster) has significant contribution to the aim of regional economic development to empower by providing job and utilizing local assets. To promote sentra industri, local government can develop participation, economic freedom, and economic satisfaction to the economic agents in sentra industri. However, the problem lies in their culture of proyek'